If x2+y2 = 1, then

(a) yy’’-2(y’)2+1 = 0

(b) yy’’+(y’)2+1 = 0

(c) yy’’-(y’)2+1 = 0

(d) none of these

Solution:

Given x2+y2 = 1

Differentiate w.r.t.x

2x + 2y (y’) = 0

Again differentiate w.r.t.x

2 + 2(y’)2 + 2yy’’ = 0

=> 1 + (y’)2 + yy’’ = 0

Hence option b is the answer.

Was this answer helpful?

 
   

0 (0)

(0)
(0)

Choose An Option That Best Describes Your Problem

Thank you. Your Feedback will Help us Serve you better.

Leave a Comment

Your Mobile number and Email id will not be published. Required fields are marked *

*

*

BOOK

Free Class

Ask
Question